Histologic evaluation of apical pulp of immature apex following extraction, surface treatment, and replantation in different storage media in dogs. Issue 2 (21st October 2014) - Jabarifar, Ebrahim; Khalighinejad, Navid; Khademi, Abbas Ali; Razavi, Seyed Mohammad; Birjandi, Neda; Badrian, Hamid; Ansari, Ghasem
Abstract Aim This study was designed to evaluate the apical pulp of open apex teeth following extraction, surface treatment, and preservation in different storage media in dogs. Materials and methods Four healthy male dogs were included in this prospective animal study. In the first phase of extraction, 30 teeth were extracted atraumatically from dogs (incisors and premolars) and then randomly divided into three groups based on different types of storage media: (i) milk, (ii) HBSS, and (iii) dry storage. In milk and HBSS groups, teeth were contaminated by dog's saliva and then kept in milk and HBSS solution, respectively, for 2 h. In the third group, teeth were stored in a dry storage for 2 h. Before replantation, all teeth were soaked in 10% doxycycline. After 2 months, in the second phase of extraction, all experimental teeth were extracted (40 teeth including control group). Three longitudinal sections (3–4 mm thickness) were stained with H&E and investigated under optical microscope. Histologic evaluations were performed, and data were analyzed using Kruskal–Wallis and Fisher's exact test (α = 0.05). Results There was a significant difference between the milk and control groups regarding the presence of the odontoblastic layer and resorption (P = 0.04). Also, there was a significant difference between dry storage and control group in the presence of the odontoblastic layer (P = 0.02). There was no statistically significant difference in other histologic factors between different groups (P > 0.05). It was revealed that there is no significant difference between different groups regarding the intensity (P = 0.06) and the type of the inflammation (P = 0.24). Also, the hyperemia showed no significant difference between different groups (P = 0.51). Conclusion It was concluded that HBSS and milk are appropriate storage media. Also, it was shown that 2 h dry storage probably does not threaten the vitality of the pulp cells.